Fifty Years of Optometric Education The Continuing Education Program of the Saskatchewan Optometric Association - Forsyth, W A (Canadian Journal of Optometry, 1983)
This paper reviews the history of the origin, development and progress of the Saskatchewan Graduate Summer Courses. It reveals the responsible attitude of those pioneer optometrists towards the need for education in the discharging of their professional responsibilities, and this prior to the acceptance of continuing education by optometry and other disciplines.